Mechanisms of Senescence and Anti-Senescence Strategies in the Skin - Evangelia Konstantinou; Eliane Longange; Gürkan Kaya (Biology)
The skin is the layer of tissue that covers the largest part of the body in vertebrates, and its main function is to act as a protective barrier against external environmental factors, such as microorganisms, ultraviolet light and mechanical damage. Due to its important function, investigating the factors that lead to skin aging and age-related diseases, as well as understanding the biology of this process, is of high importance. Indeed, it has been reported that several external and internal stressors contribute to skin aging, similar to the aging of other tissues. Moreover, during aging, senescent cells accumulate in the skin and express senescence-associated factors, which act in a paracrine manner on neighboring healthy cells and tissues. In this review, we will present the factors that lead to skin aging and cellular senescence, as well as ways to study senescence in vitro and in vivo. We will further discuss the adverse effects of the accumulation of chronic senescent cells and therapeutic agents and tools to selectively target and eliminate them.